TIRADS score is of limited clinical value for risk stratification of indeterminate cytological results. Issue 1 (July 2018) - Chaigneau, E; Russ, G; Royer, B; Bigorgne, C; Bienvenu-Perrard, M; Rouxel, A; Leenhardt, L; Belin, L; Buffet, C
Abstract : Context: Thyroid nodules with cytological indeterminate results represent a daily and recurrent issue for patient management. Objective: The primary aim of our study was to determine if TIRADS (Thyroid Imaging Reporting and Data System) could be used to stratify the malignancy risk of these nodules and to help in their clinical management. Secondary objective was to estimate if this risk stratification would change after reclassification of encapsulated non-invasive follicular variant of papillary carcinomas (FVPTC) as non-invasive follicular thyroid neoplasm (NIFTP). Patients and methods: Single-center retrospective study of a cohort of 602 patients who were referred for ultrasound-guided fine-needle aspiration from January 2010 to December 2016 with an indeterminate cytological result and in whom histological results after surgery were available. TIRADS score was prospectively determined for all patients included. Nodules that had been classified as FVPTC were submitted to a rereading of histological report and reclassified as NIFTP when judged relevant. A table of malignancy risk crossing Bethesda and TIRADS results was built before and after this reclassification. Results: The study included 602 cytologically indeterminate nodules. TIRADS score was positively correlated with the malignancy rate ( P < 0.0001). Risk stratification with TIRADS was significant only in Bethesda V nodules ( P = 0.0004). However, the risk of malignancy in this Bethesda V category was always above 45%, whatever the TIRADS score. Conclusion: For a clinician facing an indeterminate cytological result for a thyroid nodule, return to TIRADS score is of limited value in most conditions to rule in or rule out malignancy and to guide subsequent management of patients.